2006
DOI: 10.1080/13697130600865774
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hysterectomy on ovarian blood supply and endocrine function

Abstract: Hysterectomy may impair ovarian blood supply and function. There is good correlation between Doppler parameters and endocrine parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 25 publications
1
41
0
2
Order By: Relevance
“…The biologic mechanisms may relate to a combined effect of hormonal changes and the age at which the surgery occurs. Studies have shown that even with ovarian conservation, women with a hysterectomy experience changes in hormone levels and blood supply to the ovaries post-surgery [23,24] resulting in an early onset of symptoms (as evidenced in our study where hysterectomy was associated with a higher risk of early onset symptom patterns). It has been estimated that women who have a hysterectomy reach menopause around 1.9-3.7…”
Section: Discussionsupporting
confidence: 52%
“…The biologic mechanisms may relate to a combined effect of hormonal changes and the age at which the surgery occurs. Studies have shown that even with ovarian conservation, women with a hysterectomy experience changes in hormone levels and blood supply to the ovaries post-surgery [23,24] resulting in an early onset of symptoms (as evidenced in our study where hysterectomy was associated with a higher risk of early onset symptom patterns). It has been estimated that women who have a hysterectomy reach menopause around 1.9-3.7…”
Section: Discussionsupporting
confidence: 52%
“…This finding can be explained by at least 2 hypotheses (2124): 1) hysterectomy disrupts ovarian blood flow or removes paracrine or endocrine signals from the uterus (or both), thereby hastening follicular depletion and leading to earlier menopause; 2) underlying diminished ovarian reserve in women presenting for hysterectomy causes symptoms (eg, menorrhagia, leiomyoma growth, etc) prompting hysterectomy. The present study argues against the latter hypothesis because we show that women presenting for hysterectomy had similar antimüllerian hormone levels as referent women at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…In concurrence with the WHI trial we found that concomitant BSO at the time of hysterectomy does not incur additional risks of cancer . Previous studies linking hysterectomy to incident cancers have suggested that hysterectomy without BSO may interfere with ovarian blood supply and compromise ovarian function . Hysterectomy may result in increased levels of follicle‐stimulating hormone, lower estrogen and testosterone levels, and precipitate menopause as compared to women not having a hysterectomy .…”
Section: Discussionmentioning
confidence: 99%